Mutual Cooperation in the Batagak Pangulu Tradition (Information of Penhulu) in Minangkabau - Mhd Isman; Charles Butar-butar (RIRAI Publisher, 2023)
The Batagak Pangulu ritual (the prince's inauguration) is one type of Minangkabau traditional ceremonial tradition. This traditional celebration comprises customary rituals that are quite expensive. The costs could reach 100 million rupiahs or even more, depending on the size of the event that the clan members put on. utilizing a qualitative approach to data collection for this study. Sources of information include traditional leaders and Minang people who have undergone modification by researchers. The study's findings indicate that the Pangulu Batagak ceremony may be held and that the headman and clan members will cooperate to reduce the high costs. It is difficult to perform the Batagak Pangulu rite without cooperation (gotong royong). The killing and preparation of buffalo to be fed at the prince's inauguration is another example of this kind of reciprocal collaboration. Similar to how preparation takes place, mutual cooperationis evident when clan members work together to clean up the area and prepare the adat hall. The study concludes that the Batagak Panglu tradition must be preserved as an ancestral culture because doing so can help the Minang people maintain their ability to collaborate or work together in all of their endeavors.